ENVIRONMENTAL LAW AND CIVIL LIABILITY FOR DAMAGE TO THE ENVIRONMENT - Imbeloni Mattos, Thulio; Henrique Medeiros de Souza, Carlos; Moraes Marques, Bruna; Machado de Oliveira, Fabio; da Silva Monteiro, Maressa (LINKSCIENCEPLACE, 2026)
This article presents a discussion about Environmental Law and Civil Liability for Damage to the Environment. To protect the environment against disrespect and degradation of nature, Environmental Law and civil liability for environmental damage were instituted. Thus, the objective of the present work is to investigate the civil liability for damages caused to the environment. This theme is important because it aims to satisfy the needs of the community, based on the reasonableness of the use of natural resources, since the concern with the environment must be one of the driving forces for sustainable development, safeguarding a harmonious relationship between economic growth And protecting the environment. In order to answer this question, a bibliographical research based mainly on the Federal Constitution, Legislation, United Nations and renowned jurists was implemented, as well as other institutions that care about the environment. The remedying of damages to the environment presents a number of obstacles to the punishment of degrading polluters, which are often subject to reduction or elimination, through modifications favoring financial interests, mainly related to large works, overlapping the Interest in preserving or protecting, demonstrating the influence of economic factors also in the environmental area. In this sense, the State's commitment to social development that is less aggressive to nature becomes important, placing the environmental issue as one of its elements of protection, promoting social mobilization in order to preserve what exists and tries to recover what it has left behind. exist; A change of social behavior is necessary because the state is constituted and created by and for society.